2023
DOI: 10.1111/mec.17024
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolutionary change, constraints and the maintenance of polymorphism in natural populations of Drosophila melanogaster

Abstract: Allele frequencies can shift rapidly within natural populations. Under certain conditions, repeated rapid allele frequency shifts can lead to the long‐term maintenance of polymorphism. In recent years, studies of the model insect Drosophila melanogaster have suggested that this phenomenon is more common than previously believed and is often driven by some form of balancing selection, such as temporally fluctuating or sexually antagonistic selection. Here we discuss some of the general insights into rapid evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Differentiating between these adaptive and demographic hypotheses will require functional validation of the putative drivers of the sweeps (e.g. Glaser-Schmitt et al 2023 ). Functional evidence will be important for testing whether seasonal adaptation in In(2L)t is “fine-tuned” by young, habitat-specific alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating between these adaptive and demographic hypotheses will require functional validation of the putative drivers of the sweeps (e.g. Glaser-Schmitt et al 2023 ). Functional evidence will be important for testing whether seasonal adaptation in In(2L)t is “fine-tuned” by young, habitat-specific alleles.…”
Section: Discussionmentioning
confidence: 99%
“…D. melanogaster mating involves a male display performance and female acceptance or rejection. A number of experimental evolution studies (Rice 1992 ;Rice 1996 ;Audet et al 2023) and genetic studies (Innocenti and Morrow 2010 ;Cheng and Kirkpatrick 2016 ;Glaser-Schmitt et al 2023 ) have confirmed the prevalence of sexually antagonistic loci in D. melanogaster. Pleiotropic alleles that trade off between survival and male display quality may be the simplest case of antagonism to consider for a model of balancing selection, and one highly relevant to the biology of D. melanogaster.…”
Section: Sexually Antagonistic Polymorphism In D Melanogastermentioning
confidence: 96%
“…melanogaster mating involves a male display performance and female acceptance or rejection. A number of experimental evolution studies (Rice 1992;Rice 1996;Audet et al 2023) and genetic studies (Innocenti and Morrow 2010;Cheng and Kirkpatrick 2016;Glaser-Schmitt et al 2023) have confirmed the prevalence of sexually antagonistic loci in D. melanogaster. Pleiotropic alleles that trade off between survival and male display quality may be the simplest case of antagonism to consider for a model of balancing selection, and one highly relevant to the biology of D. melanogaster.…”
Section: Sexually Antagonistic Polymorphism In D Melanogastermentioning
confidence: 96%